MUD LOBSTER Thalassina (Latreille, 1806) (Decapoda: Thalassinidae) IN TANJUNG TIRAM DISTRICT SOUTH KONAWE REGENCY, SOUTHEAST SULAWESI - Muhammad Fajar Purnama; La Ode Alirman Afu (Jurusan Perikanan dan Kelautan, 2017)
This research aims to identify mudlobster species in Tanjung Tiram District, Southeast Sulawesi. Based on the identification, all specimens caught was belong to the species of Thalassina anomala (Herbst, 1804). Morphological characteristics of T. anomala distinguishing from other types Thalassina: 1) Rostrum triangular shape, rounded and serrated along its lateral border; 2) Dorsomedian tubercless on carapace extending up to the dorsal part of the first abdominal somite; 3) Abdominal sternite 2-5 on pleopod to have a tubercless in the middle (median line), 4) Pereopod 1have 13-20 tubercless on the inner side of the propodal and along the lateral side of the propodus, and 5) On males, petasma without proximal spine and rounded tip wide without setae.The finding of T. anomalain mangrove forest (intertidal zone) of Tanjung Tiram was basically cause by the distribution of this species in the world wide is widely distributed than other species from the genus of thalassina.